Integrated System Appoarch dalam pembelajaran Bahasa Arab - Baiq Wahyu Diniyati; Khoirul Mizan; Wachida Muhlis (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
In the field of education, the role of teachers is very important. Without a teacher, learning activities cannot run well. A teacher must also have sufficient competence in educating, understanding and transforming knowledge to students, to organize learning well, one of the things that teachers must pay attention to is choosing an appropriate approach. One of them is the Integrated System Appoarch (ISA). This article aims to understand the concept of Integrated System Approach (ISA) theory in learning Arabic using the library research method. The results show that the Integrated System Appoarch (ISA) can integrate all aspects of the Arabic language into one unified whole; maharah istima', kalam, qiraah and kitabah. Evidence can strengthen students' overall understanding of Arabic and enable them to use the language well in various communication situations